Avaliação da composição mineral do mosto de cana de açúcar no desempenho fermentativo com cultura mista de leveduras Saccharomyces cerevisiae diagnóstico e solução de problemas relacionados a produção industrial de etanol - Silveira, Larissa Gabriele Silva (2022)
The International Energy Agency estimates that ethanol from sugar cane reduces the emission of greenhouse gases by 89%. Brazil ranks second in world production of ethanol but still needs to improve in the coming years to reach the decarbonization targets proposed by the National Biofuel Policy. However, the process is consolidated the ethanol production improvement depends on the role performed by several factors as fermentation. Industrial yeasts are inoculated in the fermentation owing to their great fermentation characteristics but it may happen the entrance or appearance of contaminating microorganisms which are called wild yeasts. The process requires a wide range of minerals to reach adequate efficiency and a correct range of macro and micronutrients in the fermentation may improve the functioning of cellular metabolism and prevent the development of wild yeasts. This study aims to analyze the effects of mineral nutrients on ethanol production from synthetic sugarcane juice and a mixed culture of industrial and wild yeast. The industrial yeasts BG-1, CAT-1, FT-858L and PE-2 of the species Saccharomyces cerevisiae were used and the wild yeast was isolated from an Alcohol Power Plant in Goiás and called LFS. The yeasts were identified according to their macromorphological characteristics in the growth of colonies on plates. To assure the experimental reproducibility the synthetic sugarcane juice was used with 16% of sugars (m/v). The fermentation essays were evaluated by high performance liquid chromatography and residual sugars, glycerol, ethanol and acetic acid quantified. Minerals were quantified by atomic absorption spectrometry. The tests were carried out in the proportion of 30% of the wild yeast and 17.5% of each industrial yeast for 72 hours at 30ºC with 2.5 mL of the synthetic sugarcane juice. The inoculum was prepared from the scraping of the yeast present in the sterile plates and the solution mineral was added for the supplementation. The influence of Ca, Fe, Cu, K, P, N, S and Mg ions was evaluated at the end of fermentation through colony population dynamics, sugar residual and ethanol production. The tests showed that nitrogen, magnesium, sulfur and copper favor fermentation while calcium, phosphorus and iron are more prejudicial to the process. To evaluate the relationship between the prejudicial minerals was carried out a simplex-lattice mixture design with 3 components and results showed that excess calcium is prejudicial to ethanol production. Another simplexcentroid mixture design was carried out with the 4 elements identified as favorable in synthetic sugarcane juice with calcium excess and the contamination decreased by 67% with supplementation of nitrogen, magnesium and sulfur. Tests in natural sugarcane juice showed that reduction of contaminating was by 48% and confirmed that nitrogen, magnesium and sulfur are favorable to inhibit wild yeast growth. In conclusion, the tests demonstrated that supplementation of nitrogen, magnesium and sulfur reduces the contamination and increases ethanol production. As a suggestion, the addition of fertilizers with these minerals during the cultivation of sugarcane or in start fermentation may help to improve the industrial process.